Evaluation of the microstructure and dry sliding wear behaviour of thixoformed A319 aluminium alloy. (5th July 2015) - Alhawari, K.S.; Omar, M.Z.; Ghazali, M.J.; Salleh, M.S.; Mohammed, M.N.
Graphical abstract: Highlights: Thixoforming process has enhanced the microstructure and increased the hardness. Thixoformed alloy shows uniformly distributed silicon and intermetallic compounds. Thixoformed alloy shows a lower wear rate and coefficient of friction. The enhanced microstructure plays a major role in improving wear performances. Abstract: The microstructural and dry sliding wear characteristics of thixoformed A319 aluminium alloy are investigated and compared with those of a conventional mould cast alloy. Cooling slope technique was employed to produce thixoforming feedstock with pouring temperatures between 620 and 640 °C, plate lengths between 300 and 500 mm and 60° inclined angle. The optimum rheocast alloy was thixoformed at 50% liquid fraction. A pin-on-disc tribometer was used to conduct tribological tests under dry sliding conditions at 1.0 m/s sliding speed, under three loads of 10, 50 and 100 N and 9 km distance. The dendritic microstructure in the conventionally cast alloy transforms into a globular or rosette-like microstructure using cooling slope method with optimum conditions of 630 °C pouring temperature and 400 mm plate length, which gives a grain size of 34 μm and shape factor of 0.75. Thixoformed alloy microstructure shows a fine globular primary phase, fragmented and uniformly distributed silicon and intermetallic compounds. Also the thixoformed alloy exhibits improved wear resistance and lower friction coefficient in comparison to the cast alloy particularly at low load. The dominant wear mechanism is a combination of abrasive and adhesive wear at low load and plastic deformation followed by adhesive wear at high load.